LINC01271 promotes fracture healing via regulating miR-19a-3p/PIK3CA axis - Qinghua Chen; Lina Huang; Wenjun Ji; Miao Huang; Jincheng Sima; Jin Li; Hao Song; Wei Xiong; Bin Chen (Journal of Orthopaedic Surgery and Research)
Abstract Objective Osteoporosis increases the risk of fragility fractures, impacting patients’ lives. This study aimed to investigate whether LINC01271 was involved in the process of fragility fractures and healing, providing a new perspective for its diagnosis and treatment. Methods This study included 94 healthy individuals, 82 patients with osteoporosis, and 85 patients with fragility fractures as subjects. RT-qPCR was used to measure the levels of LINC01271, miR-19a-3p, PIK3CA, and osteogenic differentiation markers in osteoblasts and subjects’ serum. Luciferase reporter assays, RIP experiments, and RNA pull-down assays were utilized to verify the target relationships between LINC01271 and miR-19a-3p, as well as between miR-19a-3p and PIK3CA. Cell proliferation and apoptosis were assessed using CCK-8 assays and flow cytometry. Results Compared to the healthy control group, the serum levels of LINC01271 were significantly reduced in patients with osteoporosis and fragility fractures. Furthermore, LINC01271 levels increased with time-dependent fracture healing. In vitro studies indicated that LINC01271 boosted osteoblast proliferation, inhibited apoptosis, and augmented osteogenic differences, whereas its inhibition reverses their effects. LINC01271 and PIK3CA were identified as targets of miR-19a-3p, and overexpression of miR-19a-3p could antagonize the effect of LINC01271 in promoting fracture healing. Conclusion The results indicated that LINC01271 may play a key role in osteoblast function and fracture healing through its interaction with miR-19a-3p and regulation of PIK3CA.